2012
DOI: 10.1051/ita/2012005
|View full text |Cite
|
Sign up to set email alerts
|

Easy lambda-terms are not always simple

Abstract: Abstract. A closed λ-term M is easy if, for any other closed term N , the lambda theory generated by M = N is consistent. Recently, it has been introduced a general technique to prove the easiness of λ-terms through the semantical notion of simple easiness. Simple easiness implies easiness and allows to prove consistency results via construction of suitable filter models of λ-calculus living in the category of complete partial orderings: given a simple easy term M and an arbitrary closed term N , it is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In Section 2.4.1 we indicate how some of the most known classes of webbed models are recovered as particular instances of i-models (more details for Filter Models are in [12]). Along these lines the notion of partial i-web generalizes those of partial pair [6] (related to graph models) as well as the notions of partial webs of the other types.…”
Section: Definition 42mentioning
confidence: 99%
See 1 more Smart Citation
“…In Section 2.4.1 we indicate how some of the most known classes of webbed models are recovered as particular instances of i-models (more details for Filter Models are in [12]). Along these lines the notion of partial i-web generalizes those of partial pair [6] (related to graph models) as well as the notions of partial webs of the other types.…”
Section: Definition 42mentioning
confidence: 99%
“…If the EATS satisfies condition ( * ), then the function φ : P f (A) × A → A given by φ (a, α) = ( a) → α is a b-morphism, and hence an i-web A = (A , φ ). The corresponding filter model is exactly the i-model A + (see [12] for the details).…”
Section: Well-known Instances Of I-websmentioning
confidence: 99%
“…Since their introduction, intersection types have played a role of increasing prominence in programming languages research. From completeness of type assignment [BCD83], to characterization of strongly normalizing (and weakly normalizing) terms [DG03], to syntactic presentations of domain models [AC98], including graph models and filter models [Roc18], to classifications of certain classes of easy terms [CS12], to using types to count resources [KV17], and many others -the theory of intersection types is now a well-established research field of type theory.…”
Section: Introductionmentioning
confidence: 99%
“…Studying C-easiness gives insights on the expressive power of C. Concerning filter lambda models [8], for instance, it had been conjectured [3] that they have full expressive power for easy terms, in the sense that any easy term was conjectured to be filter easy. Carraro and Salibra [20] showed that this is not the case: there exists a co-r.e. set of easy terms that are not filter easy.…”
Section: Introductionmentioning
confidence: 99%